Geographical proximity and circulation of knowledge through inter-firm cooperation - André Torre; Delphine Gallaud (European Regional Science Association (ERSA), 2004)
The production of scientific and technological innovations has become essential for many firms, but the latter are seldom in possession of all the knowledge needed for this activity because of the increasing complexity of knowledge bases or because R&D departments are too small. As they do not possess internally all the skills they need, firms wishing to innovate have recourse to external sources, such as cooperation with other firms or public organizations of research. However, acquiring external knowledge is not sufficient; one must also be able to use it in a specific process of production, to transform it into organizational routines, because it is important not only to integrate this knowledge, but ideally to use it to produce new knowledge. This process of creation, re-creation or imitation of new resources not only necessitates several technical and organizational adaptations, but also requires frequent relations of cooperation and partnership. The integration of new knowledge cannot be done in one go, but progressively during the course of the innovation projects, which implies that relations be sustained for a period of time. But the interests of the participants to this interactive process, as well as their opinions concerning technical issues sometimes vary or diverge. This is why co-operations are also sources of tensions and conflicts that jeopardize the adaptation of knowledge produced somewhere else to the context of the firm or even completely hinder the innovation process. In this paper, we try to provide some answers to the following question: What is the role played by geographical and organized proximities in the context of these external acquisitions of knowledge? In other words, can they help reduce the intensity of conflicts and thus facilitate the interactive process of innovations? First, we present shortcomings of innovation theory and works on spillovers claiming the importance of geographical proximity for circulation of knowledge without considering organizational prerequisites to reach this impact. Having explained the relevance of permanent as well as temporary geographical proximity, we will then turn to a discussion of conflicts between cooperators within innovation processes from a theoretical as well as an empirical perspective. The empirical study is based on a case study of French biotechnology firms and will serve to prove our hypothesis that temporary geographical proximity play an important role in preventing and resolving conflicts between innovators.
Keywords: 330